A study on the association of psychiatric diagnoses and childhood adversities with suicide risk. (17th February 2019) - Salokangas, Raimo K. R.; Luutonen, Sinikka; Heinimaa, Markus; From, Tiina; Hietala, Jarmo
Abstract: Background : In addition to psychiatric disorders, childhood adversities may increase the risk of suicidal behavior. In previous studies, the effects of clinical co-morbidity and overlap of childhood adversities has rarely been taken into account. Aim: The study aims to search associations of psychiatric diagnoses and childhood adversities and trauma (CAT) with suicide risk. Methods: Altogether 415 adult patients attending primary and psychiatric outpatient care filled in the Trauma and Distress Scale, including assessment of five core CAT domains (emotional, physical and sexual abuse, and emotional and physical neglect). The study patients' current psychiatric disorders and suicide risk were assessed by the Mini International Neuropsychiatric Interview. Results: Age, poor perceived health, poor social support, current psychiatric treatment, all psychiatric disorders, except hypomania, emotional and physical abuse, and emotional neglect did associate significantly with suicide risk. Number of psychiatric disorders and CAT domains had dose-dependent effects on suicide risk. In multivariate analysis, current psychiatric treatment, current and life-time major depression, social phobia, alcohol, and drug dependency, as well as emotional abuse had direct associations with suicide risk. In females, manic disorders and drug dependence, and in males, dysthymia, social phobia, and emotional abuse associated with suicide risk. Conclusions: Psychiatric disorders and most CAT domains associate with suicide risk. However, when the effect of co-morbidity and overlap of CAT domains is controlled, major depression, social phobia, alcohol, and drug dependency and emotional abuse seem to increase the risk of suicide. The risk profile varies between the genders.